Oral participation practices in classroom among university students in Afghanistan - Hamza Atifnigar; Hedayatullah Bawar; Malang Momand; Siti Aishah Abdul Hamid (Institute of Advanced Engineering and Science, 2022)
This study aimed at exploring factors affecting classroom participation among students in the English department of Laghman University, Afghanistan. More precisely, this research discovered factors related to teachers and class-size that hinder students’ practice of oral participation in the classroom. In collecting the data, this study employed mixed-method research with concurrent design. An adapted questionnaire and a semi-structured interview have been used as the data collection instrument of this study. An online survey questionnaire was conducted with 110 respondents. In addition, a semi-structured interview was conducted with five of the respondents at the English Department of Laghman University. The data from the questionnaire was descriptively analyzed through using statistical package for social science (SPSS), and the semi-structured interview data were thematically analyzed and interpreted. The findings revealed that class-size related factor is the first influential factor in affecting oral participation among students and it is due to having large number students in a class. Teacher’s related factor is the second influential factor that affects the oral participation of students. Majority claimed that teachers’ approach, behavior, and qualification have prominent impact on their level of oral participation. Based on the finding, it can be seen that class-size related, and teachers’ factors affected oral participation of the students at the English Department of Laghman University. It is recommended that the Ministry of Higher Education of Afghanistan strive to decrease the number of students in each class and enforce teachers in implementing a student-centered learning approach while teaching.